Análisis financiero integral y la rentabilidad a la distribuidora delgado en el periodo 2011 - 2012 - Romero Guzmán, Lilian de los Ángeles (2016)
The present work of Thesis titled Integral Financial Analysis and the Profitability to the Thin Distributor in the period 2011 - 2012, for their exercise thought about as objectives to carry out an integral financial analysis and study of the profitability so much economic as financial to the Thin Distributor, in the period understood among the years 2011 and 2012,que it allows to measure the yield of the investments, to execute the vertical and horizontal financial analysis with the purpose of knowing the financial structure of the company like the financial position so much to the date of the financial states that is analyzed, the indicative EVA and DUPONT that he/she allows to know the added value of the company and the profitability of the same ones to present a proposal of improvement based on the obtained results of the application of the integral financial analysis and the grade of the economic and financial profitability, for the execution of these objectives a methodology was used that integrate all the methods of the financial analysis, by means of the use of the vertical, horizontal analysis, reason financial, analysis of tendencies. The general results are expressed this way: the analysis vertical evidence that the asset in the year 2011 that the total of assets registers a value of USD 1,266,340.33; the same one that is confirmed by 90.26% in average asset, 9.74% in fixed asset, the passive one is of USD 217,533.08 the same one that is integrated by the passive current whose I mount it is USD 112,910.20 represented with 8.92% and the passive long term with the USD 104,622.88 that it constitutes 8.26%, with regard to the patrimony the most important bills they are: social capital whose the I mount it is of USD 869,745.11 what constitutes 82.93%, care that one gives for the carried out contributions; the bill utility or loss of the exercise the revenues are constituted for the I mount of USD 1,167,622.60 that it represents the 100.00, the expenses they are confirmed by the value of USD 47,892.69 the same one that is divided in operational expenses with the USD 33,645.67 that it is equal to 70.25% for the year 2012 the average asset represented 92.24% I activate fixed 7.76% passive 32.52% patrimony 67.48% the revenues and expenses were represented this way, operational revenues 100%, costs 86.97% expenses 13.03% with regard to the passive long term, an increase of the USD is evidenced 48,520.00 representing 46.38% since the company has canceled more than 50% of the credit granted by a financial institution of the town, existing a reason of 1.46 what means the times that it has diminished in relation to the 2011 the tendency analysis for the calculated years is the following ones: 128,27% in the average asset, 100.00% activates fixed as for the total of active in what refers to total passive and patrimony presents the following percentages: passive current with 322.22%the passive long term 146.38% and lastly the patrimony 102.26%, what means that there has been an increase and in the balance of the departure with regard to the year considered as base the analysis of fluctuations the variations among the year 2011 and 2012 as for the average asset, the biggest change that one gives is in the bills and documents to get paid - currents that it maintains a higher rotation that skirts the 1.30 times adult to one what is truly in agreement to the standards and the bill box - banks since the distributor begins a stage of growth. in what concerns to the fixed assets, the change is significant in the active vehicles, team of transport and coalminer they rotate since a single time that represents the 1 times, they stay the same values in the passive one the variation or rotation is since of 2.38 the obligations with suppliers they were very high what represents USD 213,607.06 whose value is pondered inside the patrimony the capital had a significant value of 1.02 and the utility of the exercise that it presents for the two periods object to study they are negative since it presents loss in the state of results in the year 2011 - 2012 as more important item can observe that it is purchases that it maintains a rotation of the 1.16 in relation to the cost it occupies the highest place keeping in mind the other bills, this is due to that the distributor invests good part of its sales in getting its clients' bigger welcome by means of the quality, the second item in importance is the gross utility that occupies a 2.61veces of rotation, the application of financial indicators for the year 2011 the liquidity of the thin distributor for each dollar of effective obligation it had USD 10.12 to support it, that is to say that of a hundred percent of their revenues, 84.52% is for payment of its obligations and so alone he had left 15,48% available, with regard to the year 2012 can say that its liquidity increase, already before dedicated 84,52% of the total its revenues to cover its obligations, on the other hand now alone it dedicates 80,65% for the back of the same ones we can observe that for the year 2012 this capital of work increase in USD 1,102,343.37, reason why it can be consequence of the plan of investments executed by the distributor, it proves sour it is observed that this indicator increase but enough he/she doesn't stop to be able to assist the total of its average obligations without necessity of selling its inventories. on the other hand year 2012 the distributor would not reach to assist its obligations and he/she would have to liquidate part of its inventories to be able to complete the company it depends directly on the sale of its inventories to be able to assist its average obligations, indicator of activity number of days wallet by hand the term average granted to the clients so that they carry out the payment of the orders it is approximately of 7 days in the year 2011 and of 4 days for the year 2012, wallet rotation the thin distributor that for the year 2011 broken its wallet cash 51.43 times in the year that is to say that on the average slow 45 in rotating its wallet, on the other hand in for the year 2012 this process was quick, rotation of inventories converted the total of its inventories cash or in bills to get paid 0.94 times for the year 2011 and 0.73 times for the 2012pudo to be for the increase of the sales, rotation average assets for the year 2011 the distributor achievement to sell USD 1.02 for each dollar invested in active operational, and for the year 2012 the company achievement to sell USD 0.86 for each dollar invested in active operational, rotation fixed assets can conclude that the company for the year 2011 broken its asset fixed 9.47 times and for the year 2012 reach 0.86 times, indebtedness on total assets can conclude that the participation of the creditors for the year 2011 are of 17.18% and for the years 2012 are of 32.52% on the total of the assets of the company; that which is not a very risky level, profitability of the patrimony allows us to conclude that the profitability of the gross patrimony for him years 2011 and 2012 were respectively of 10.32% and 23.26%; that is to say that there was an increase in the profitability of the investment of the partners of 12.94%, this probably originated by the increment of the appraisements of the company, gross margin of the above-mentioned utility can infer that for the year 2011 and 2012, the gross utility obtained after discounting the costs of sales was respectively of 15.34% and 37.07% for which observe that a light ascent descent of 21.73% exists for this period, as well as we can affirm that although the sale costs increased its impact about the gross utility it is not significant, net margin of utility exists a decrease of 16.93% in the utility, additionally we say that in spite of the increase in the sale costs and in the administration expenses and sales, the sales grew enough to assume this increase, system DUPONT in the year 2012 in the Distributor Thin sample a level of solvency or profitability on the patrimony under good conditions The EVA by means of the application of the (value economic attaché) you concludes that the thin distributor, once paid the financial and deduced expenses the cost of opportunity of the own capital generates an added value of USD 1,440.00; because the profitability of the assets is superior at the capital cost, that which allows to cover the prospective minimum profitability, with the utility that oscillates 179,062.14 that which has been able to reward the cost of the products the landlady has invested. Therefore you concludes that the company in the analyzed years has an acceptable financial structure because the concentration bigger than its bills this in the inventories that are the reason of the commercial operation of the company, however the indexes of liquidity and profitability, they are not the most appropriate, but even the indexes of indebtedness for what the company is in a high financial risk, therefore it is recommended to improve the administration of the capital, an appropriate rotation of sales and the immediate collection of bill collection slopes that allow to pay the financial situation of the company.